Sei sulla pagina 1di 13

lim

n+

sin 1 1

1

n

= 1

1 cos 1

n 1

=

sin

1

n

1

n n

1

2

2

2

= 0

lim

n+

lim

n+1

n

n+ n! = +

lim

n+n n = +

lim

lim

n+

n

q

n k = + q ]1; +[, k R

lim

n+

n

q

n k = 0 q ] 1; 1[, k R

q

n

lim

n+n!

= 0 q R

lim

n+

n n! n = 0

n+ 1 +

lim

n n

1

= e

lim

n+

log 1 +

1

n

1

n

= 1

lim

n+

1

e n 1

1

n

= 1

 

a n < +

   

lim

n→∞ a n = 0

nN

 

|S n+k S n | <

   

a n < +

 

nN

a n

   

a n < +

nN

nN

b n a n

b n < +

 

a n < +

 

nN

nN

lim

n+

a

b

n

n

 

= L ]0; +[

   

a n b n

lim

n+

a n = L [0; 1[

n

   

a n < +

 

nN

lim

n+

a n = L ]1; +]

n

   

a n = +

 

nN

lim

a n+1

= L [0; 1[

 

nN

a n < +

n+

a

n

lim

a n+1

= L ]1; +[

 

nN

a n = +

n+

a

n

a n 0 a n a n+1 n N

 

a n < +∞ ⇔ 2 n a 2 n < +

 

nN

nN

{B n } n a n 0 a n a n+1

n N

 

(a n b n ) < +

 

nN

 

f

lim

f(x)0

sin f (x) f(x)

= 1

lim

f(x)0

1 cos f (x)

= 1

2

f(x) 2

lim

f(x)0

sin f (x) f (x)

f(x) 2

= 0

f(x)+f(x) f(x) = +

lim

lim

f(x)+

q f(x)

f(x) k

= + q ]1; +[, k R

lim

f(x)+

q f(x)

f(x) k

= 0 q ] 1; 1[, k R

f(x)+ 1 +

lim

f(x) f(x)

1

= e

log (1 + f (x))

f(x)

e f(x) 1

f(x)

= 1

lim

f(x)0

= 1

lim

f(x)0

k R

=

x a , a

= 1

=

1

 

=

x

e x

=

sin x

=

cos x

=

tan x

=

log x

=

sinh x

=

cosh x

=

tanh x

=

arcsin x

=

arccos x

=

arctan x

=

a x

=

log a x

=

x

=

0

ax a1

1

 
 

x

2

e x

cos x

sin x

1 + tan 2 x =

1

x

cosh x

sinh x

1 tanh 2 x =

 

1

1 x 2

 

1

1 x 2

1

cos 2 x

1

cosh 2 x

1

1 + x 2 a x log a

1

x log a

1

2 x

f(x) a , a

= 1

=

1

f(x)

=

e f(x)

=

sin

f (x)

=

cos

f (x)

=

tan

f (x)

=

log

f (x)

=

arctan f (x)

=

f(x)

=

af (x)f(x) a1

f (x)

f(x) 2

f (x)e f(x)

f (x) cos f (x)

f (x) sin f (x)

f (x)

cos 2 f(x) f (x)

f(x)

f (x)

1 + f(x) 2

f (x)

2 f(x)

 

(f · g)(x)

=

(f

+

g)(x)

=

 

f(x)

g(x)

=

(g

f )(x) = g(f (x))

=

f (x) · g (x) + g(x) · f (x)

f

(x) + g (x)

f (x)g(x) g (x)f(x)

g(x) 2

f (x)g (f (x))

e x

=

log(1 + x)

=

sin x

=

cos x

=

tan x

=

arcsin x

=

arccos x

=

arctan x

=

1

 

=

1 x

(1 + x) a

=

sinh x

=

cosh x

=

tanh x

=

1

+ x + x 2 +

2

x x 2 + x 3

2

3

x x 3! 3

+ x 5! 5

1 x 2! 2

+ x 4! 4

+

n

x n! + o(x n )

n

+ (1) n1 x n + o(x n )

+ (1) n x 2n+1

(2n + 1)! + o(x 2n+2 )

+ (1) n

x 2n

(2n)! + o(x 2n+1 )

x

3

2x 5

x +

x + 1

2

3

x

15

+ 2 · 4

+

3

+

1 · 3 x 5

o(x 6 )

+

3

5

π

2

x 1

2

1 · 3 x 5

x

3

3

2 · 4

5

+ (2n 1)!!

x

2n+1

2n + 1 + o(x 2n+2 )

x

2n+1

(2n)!!

(2n 1)!!

2n + 1 + o(x 2n+2 )

(2n)!!

x x 3

3

+ x 5 5

x

2n+1

+ (1) n 2n + 1 + o(x 2n+2 )

1 + x + x 2 +

+ x n + o(x n )

1 + ax + a(a 1) x 2 +

x 5

x

n

(a n + 1) x n! + o(x n )

2

+

+ a(a 1)

x

2n+1

+ x 3! 3

+

5! +

(2n + 1)! + o(x 2n+2 )

x 2 + x 4

1 +

2!

+

4!

2x

5

+

x

x 3

3

15

x

2n

+

(2n)! + o(x 2n+1 )

+ o(x 6 )

b

= 0 k R a

= 1 c > 0

k =

=

1

=

x

x a

kx

x a+1

a + 1

log |x|

e x

sin x

cos x

tan x

log x

sinh x

cosh x

tanh x

arcsin x

arccos x

arctan x

1

x 2 + b 2

1

x 2 b 2

x

x 2

+ k

x 2 + k

c x 2

1

b x 2

1

c x 2

=e x

=

=

=

=

=

=

=

=

=

=

=

cos x

sin x

log | cos x|

x(logx 1)

cosh x

sinh x

log cosh x

arcsin x + 1 x 2

arccos x 1 x 2

arctan x log 1 x 2

1 b arctan x b 1 |x − b| 2b log |x + b| log
1 b arctan x
b
1
|x − b|
2b log
|x + b|
log x 2 + k
1 b arctan x
k
c
x
(arcsin √
c − x 2 )
2
c + x c
log |x + x 2 + b|
x
arcsin
c

=

=

=

=

=

=